Tragedy in Aurora: the culture of mass shootings in America - Diaz, Tom (Rowman & Littlefield, 2019)
Prelude -- The maple leaf and the eagle -- When Lonnie met Sandy -- Over the double rainbow -- Tobacco road -- Only in America -- The right not to be shot -- No easy answers.